Rescue ALPPS: Intraoperative Conversion to ALPPS during Synchronous Resection of Rectal Cancer and Liver Metastasis - Terence Jackson; Kelly A. Siegel; Christopher T. Siegel (Case Reports in Surgery)
Future liver remnant (FLR) is the most important deciding factor in planning for liver resection. Portal vein embolization (PVE) was first introduced in the 1980s to induce liver hypertrophy, enabling removal of multiple/bilobar tumors. PVE was later combined with sequential hepatectomies with the aim of allowing the liver remnant to hypertrophy (15–20%) between procedures. However, the interval between the two procedures (3–8 weeks) put patients at risk for disease progression. With portal vein ligation alone or when combined with sequential hepatectomy, there is also a risk for inadequate liver hypertrophy because of intrahepatic portal collaterals leading to a high (19–30%) dropout rate. The ALPPS procedure (associating liver partition and portal vein ligation for staged hepatectomy) was recently developed as a feasible means to perform extensive/bilobar liver resections. It produces rapid, enormous hypertrophy of the remnant, making previously unresectable lesions resectable. Indications for ALPPS include any extensive liver resection with inadequate FLR. Here we present a novel indication for ALPPS as a rescue when inadequate FLR was faced intraoperatively, during a simultaneous resection of rectal primary and liver metastasis.